Observance of adverse reactions and analysis of biosafety compliance in the rectal application of ozone therapy in COVID-19 Cuban patients with acute infection or convalescent - Lizette Gil del Valle; Mario M. Delgado Guerra; Ana L. Carballo- Reyes; Joniel A. Sánchez Márquez; Olga E. López Fernández; Faustina Fonseca Betancourt; Zullyt Zamora-Rodríguez; Lidia A. Fernández García; Rodolfo Suárez Iznaga; Raiza Martinez Casanueva; Lisandra Castro de la Fe; Niorkidis Gonzalez Carvajal; et al. (GarVal Editorial Ltda., 2021)
Context: Patients with COVID-19 present different biochemical and metabolic alterations from the acute state of infection until months later with variability of symptoms and increased toxicity of drugs related to oxidative stress according to previous studies. There are various alternatives to modulate oxidative stress, including the use of medical ozone, which rectal way requires observing both compliance with biosafety measures and adverse reactions in patients. Aims: To evaluate compliance with biosafety measures and the possible manifestations of adverse events in the rectal application of ozone therapy in patients with acute infection or convalescent of COVID-19. Methods: Descriptive, longitudinal studies in two clinical trials conducted at the Ernesto Guevara Hospital and the Salvador Allende Hospital, from May to July 2020. Rectal ozone therapy was applied to patients in two trials with a cycle of up to 20 applications according to the study. The activities were described and the performance of the professionals in the procedure was evaluated through an observation guide. Patient follow-up and surveillance for potential adverse reactions were performed. Results: 80% (28/36) of the patients reported the feeling of fullness of the intestines, without other reports, in no case treatment was required. The evaluation of the practices showed full compliance with the procedures without transmission of infection during the period. Conclusions: Compliance with good practices and biosafety in the rectal application of ozone results in the adequate performance of the protocols with benefit and safety for patients under treatment.